STRATIFIKASI SOSIAL, SISTEM KEKERABATAN DAN RELASI GENDER MASYARAKAT ARAB PRA ISLAM - Edi Darmawijaya (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
This paper comes from the notion that Islamic law involved with human history - in this context, with Jahiliyyah-law, is a cultural phenomenon and can be investigated by using a humanities approach and methodological tools. 1 With all the advantages and disadvantages, the study of social change by Islamic law on the law of Jahiliyyah as the background of its appearance, the one becoming the focus of the discussion in this paper, is attempted to keep away from the at- titude, the one Richard C. Martin called as fideistic scientific subjectivism or objectivism. 2 More importantly, the one portraying Islam position on mustadl'afin become a important awareness which is critical towards the social changes by Islamic law in the society.